Antioxidant activity and total phenolic and flavonoid contents of Dendrobium amoenum Wall. ex Lindl. - Poudel, Mukti Ram; Chand, Mukesh Babu; Karki, Namrata; Pant, Bijaya (Botanica Orientalis: Journal of Plant Science, 2015)
Dendrobium amoenum has biologically active phytoconstituents valued for traditional Chinese or folk medicine as tonic. Total phenolic and flavonoid contents of its stem extract was estimated by using Folin-Ciocalteu’s reagent and Aluminium chloride methods respectively. Antioxidant activity was determined by DPPH free radical scavenging method. Total phenolic content found in acetone (134.34 μg GAE/mg extract) and chloroform (101.55 μg GAE/mg extract) extract was significantly higher than other solvent extracts. Similarly, these two extracts had significantly high flavonoid content (acetone: 115.73 μg QE/mg extract, and chloroform: 84.16 μg QE/mg extract). Presence of high phenolic and flavonoid contents in these extracts showed the highest antioxidant activity. Highest antioxidant activity of these extracts was determined by their lowest IC50 value (acetone: 53.19 μg/ml and chloroform: 36.48 μg/ml). Significant negative relationship was found between phenolic content and IC50 (R2 = 0.209, p < 0.01) and flavonoid content and IC50 (R2 = 0.389, p < 0.01), which indicates high antioxidant activity due to high phenolic and flavonoid contents. This result revealed that D. amoenum act as an antioxidant agent due to its free radical scavenging activity which plays a crucial role in the development of new chemotherapeutic agents.